Functional outcome of total hip arthroplasty after a previous hip arthroscopy: a retrospective comparative cohort study. Issue 4 (July 2019) - Jain, Mikhil V; Rajpura, Asim; Kumar, Venkatesan Sampath; Shaw, Debbie; Najjar, Majeed Al; Kalsi, Navjit K; Hakimi, Mounir; Selvaratnam, Veenesh; Jackson, Richard; Board, Tim N
Background: Despite patients demonstrating significant short-term clinical improvement from a hip arthroscopy (HA), a number of patients progress to significant osteoarthritis of the hip requiring total hip arthroplasty (THA). This study aims to evaluate if there is any difference in the functional outcome of patients undergoing THA after a previous hip arthroscopy compared to patients undergoing THA for primary osteoarthritis of the hip. Methods: Between 2010 and 2013, in a group of 414 patients who underwent hip arthroscopy, we identified 18 patients who underwent a subsequent uncemented THA. These formed the study group. During the same period, 625 patients underwent an uncemented THA performed for primary OA, of which 63 patients were matched to the study group for age, follow-up and implants used. These formed the control group. Pre-op and post-op Oxford Hip Scores (OHS) were recorded for all patients. Results: A mean follow-up of 26.5 and 26.3 months was observed in the study and control groups respectively. The median (interquartile ranges) preoperative OHS were 14 (8.25, 17.0) and 18.5 (13.25, 24.75) in the 2 groups. Corresponding postoperative scores were 40 (31.25, 45) and 46 (43, 48). Median difference between the preoperative and postoperative OHS was 27 (19, 31) and 25 (18.25, 31). Adjusting for the pre-treatment scores, the postoperative scores in the study arm were significantly lower than for the control arm with an estimate (SE) of −0.464 ( p = 0.012). Post-hoc power analysis showed that the study was sufficiently powered to detect a meaningful difference in scores. Conclusion: Total hip arthroplasty after hip arthroscopy leads to satisfactory functional outcomes. However, the functional outcome in this group is significantly worse than in a matched cohort of patients undergoing THA for osteoarthritis. There was no difference in the rate of complications between the 2 groups.